2010
DOI: 10.1523/jneurosci.0124-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Cadherins Celsr1-3 Differentially Regulate Migration of Facial Branchiomotor Neurons in Mice

Abstract: During hindbrain development, facial branchiomotor neurons (FBM neurons) migrate from medial rhombomere (r) 4 to lateral r6. In zebrafish, mutations in planar cell polarity genes celsr2 and frizzled3a block caudal migration of FBM neurons. Here, we investigated the role of cadherins Celsr1-3, and Fzd3 in FBM neuron migration in mice. In Celsr1 mutants (knock-out and Crash alleles), caudal migration was compromised and neurons often migrated rostrally into r2 and r3, as well as laterally. These phenotypes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
155
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(166 citation statements)
references
References 57 publications
9
155
2
Order By: Relevance
“…Roles of the Wnt/PCP pathway in cell migration have been reported in several different contexts [24][25][26][27][28][29][30][31][32]. In this work, blocking the Wnt/PCP pathway decreased the number of NPCs that reached the OB, without affecting their differentiation or proliferation (Figs.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Roles of the Wnt/PCP pathway in cell migration have been reported in several different contexts [24][25][26][27][28][29][30][31][32]. In this work, blocking the Wnt/PCP pathway decreased the number of NPCs that reached the OB, without affecting their differentiation or proliferation (Figs.…”
Section: Discussionsupporting
confidence: 54%
“…Furthermore, the migration of facial branchiomotor (FBM) neurons [24][25][26][27][28][29][30][31] and neural crest cells [32] depends on the function of the PCP genes, as does neuronal morphogenesis in the postnatal hippocampus [33,34] and OB [35], indicating that PCP signaling is involved in the migration and differentiation of many types of neural cells [36][37][38]. However, the function of this signaling pathway in the postnatal migration and differentiation of neurons in the OB has not been clearly demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…In future work, it will be essential to identify the transcriptional targets of REST and characterize their role in FBMN migration. Interestingly, a survey of the human genome (Johnson et al, 2007) has identified REST binding sites near several genes implicated in FBMN migration, including CELSR3 (Qu et al, 2010), contactin 2 (also known as TAG1) (Sittaramane et al, 2009) and those encoding components of the DAB1/reelin/CDK5 signaling pathway (Ohshima et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that Celsr1-3 work together to regulate facial branchiomotor neuron (FBM) migration [49] . Celsr1 is expressed in FBM neuron precursors and the floor plate, but not in FBM neurons, which helps to specify the direction of FBM neuron migration in a noncell autonomous manner.…”
Section: Cooperative Actions Of Celsr1-3 In Neural Developmentmentioning
confidence: 99%
“…Single-Celsr knockout mice show different phenotypes, such as the failure of axonal projections in Celsr3-/- [38] , abnormal organization of ependymal cilia in Celsr2-/- [50] , and improper neuronal migration in Celsr1-/- [49] . However, …”
Section: Summary and Prospectsmentioning
confidence: 99%